Марксистская этика: [учебное пособие для вузов / А. И. Титаренко и др.] - Титаренко Александр Иванович (Политиздат, 1986)
Экземпляры: КХ (20240522) / Инвентарный номер: 883119 / Сис.шифр: 1МИ7 / Авт.знак: М 27 / ГРНТИ: 02 / ББК: 87